2020
DOI: 10.1002/erv.2795
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to supporting young people with eating disorders during their transition to, and time at, university: An exploration of clinicians' perspectives

Abstract: Background: Eating disorders (EDs) are common in student populations and present formidable challenges as to how best to treat and support these young people, especially at points of transition. Yet research exploring these challenges is lacking, particularly from the perspective of those providing treatment and support. Methods: A qualitative design was used to explore clinicians' perspectives of supporting students with EDs. Twelve clinicians from a large ED service in the United Kingdom participated in one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…College‐age individuals represent an age group with high prevalence of EDs where the median age of onset of BED is 21 years and the median age of onset for both BN and AN is 18 years (Hudson et al, 2007). Life transitions and increased stress during the college years have been found to be associated with heightened risk for ED development during this period of life (Ganson et al, 2021; Sawyer et al, 2018; Webb & Schmidt, 2021), and previous research on this population has suggested that the prevalence of EDs among college students ranges from 8% to 17% (Hoerr et al, 2002; Kirk et al, 2001; Prouty et al, 2002; Reinking & Alexander, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…College‐age individuals represent an age group with high prevalence of EDs where the median age of onset of BED is 21 years and the median age of onset for both BN and AN is 18 years (Hudson et al, 2007). Life transitions and increased stress during the college years have been found to be associated with heightened risk for ED development during this period of life (Ganson et al, 2021; Sawyer et al, 2018; Webb & Schmidt, 2021), and previous research on this population has suggested that the prevalence of EDs among college students ranges from 8% to 17% (Hoerr et al, 2002; Kirk et al, 2001; Prouty et al, 2002; Reinking & Alexander, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…People often hear about eating disorder treatments on social media and, as such, social media needs to be utilised to let people know about the availability and utility of programme‐led and focused interventions. Evidence‐based, targeted messaging was suggested to encourage people to get to the point when they are thinking about treatment and could help to overcome some common barriers to help‐seeking, such as down‐playing of illness severity and less perceived ability of others to help (Radunz et al., 2022 ; Webb & Schmidt, 2021 ). Involving people with lived experience is critical at every step, especially when it comes to spreading the word on social media.…”
Section: Increasing Access To Programme‐led and Focused Interventionsmentioning
confidence: 99%
“…Tertiary education in some countries may be some distance from home. This can make the transition to new services more hazardous as discussed by Webb & Schmidt, 2021. Lifespan services can bridge these gaps and provide a variety of interventions matching developmental rather than chronological age (Voderholzer et al, 2020).…”
Section: Care Pathwaysmentioning
confidence: 99%